Tooth microstructure and feeding biology of the brittle star Ophioplocus januarii (Echinodermata: Ophiuroidea) from northern Patagonia, Argentina. - Brogger, Martín I. (2015)
Ophioplocus januarii is a common brittle star on soft and hard substrates along the Argentinian and Brazilian coasts. Based on stomach contents, tooth microstructure and field observations we identified its food. Opposed to previous suggestions, O. januarii appears to be a microphagous species feeding on macroalgal fragments (found in 60.0 % of the analyzed stomachs with content), plant debris (28.0 %), animal cuticle structures (13.0 %), and unidentifiable material (30.7 %). Less frequent items found were foraminiferans, ostracods, an amphipod, a juvenile bivalve, and other crustaceans. Electronic microscope revealed digested material, diatoms and small crustacean appendices. Thus, O. januarii is an omnivorous species, feeding mainly on algae, complemented opportunistically with other items. Suspension feeding was observed in the field. It has an fenestrated arrangement intermediate between the previously described uniform and compound teeth.